2010
DOI: 10.1128/ec.00351-09
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Kinase Inhibitor Analog 1NM-PP1 Reveals a Role for Toxoplasma gondii CDPK1 in the Invasion Step

Abstract: Toxoplasma gondii CDPK1 (TgCDPK1) was found to be the target of the toxoplasmocidal compound 1NM-PP1. When TgCDPK1 was mutated at position 128 from glycine to methionine, resistance was gained. Inhibition of gliding motility without inhibition of micronemal secretion by 1NM-PP1 suggests a function for TgCDPK1 in gliding motility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
62
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 25 publications
2
62
1
Order By: Relevance
“…Support for this model is provided by inhibition of PKG with Compound 1 (15,17), and selective inhibition of CDPK1 with pyrazolopyrimidine inhibitors (8,47). Both classes of compounds offer promise for development of alternative therapeutics, given the essential nature of these kinases and the potent and specific inhibition offered by these respective chemical scaffolds (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Support for this model is provided by inhibition of PKG with Compound 1 (15,17), and selective inhibition of CDPK1 with pyrazolopyrimidine inhibitors (8,47). Both classes of compounds offer promise for development of alternative therapeutics, given the essential nature of these kinases and the potent and specific inhibition offered by these respective chemical scaffolds (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…A Tet-inducible knockout of TgCDPK1 blocks the secretion of micronemes, which results in impaired gliding motility, invasion, and egress (Lourido et al, 2010). Several specific inhibitors were designed against TgCDPK1, including pyrazolopyrimidine derivatives for which a gatekeeper mutant was shown to restore microneme secretion in the presence of the drug (Johnson et al, 2012;Kieschnick et al, 2001;Ojo et al, 2010;Sugi et al, 2010).…”
Section: Microneme Secretion and Egressmentioning
confidence: 99%
“…BKIs selectively inhibit analog-sensitive kinases, which contain a small amino acid at the gate site of the ATP binding pocket and are rare in mammalian genomes [1]. Using in silico prediction, we found that T. gondii calcium-dependent protein kinase 1 (TgCDPK1), which has a glycine residue at the gate site of the ATP binding pocket, was the main T. gondii analog-sensitive kinase [12]. In silico prediction, an in vitro culture assay using transgenic parasites, and a structural analysis of TgCDPK1 all showed that TgCDPK1 is a target of BKI [6,8,12].…”
mentioning
confidence: 99%
“…Using in silico prediction, we found that T. gondii calcium-dependent protein kinase 1 (TgCDPK1), which has a glycine residue at the gate site of the ATP binding pocket, was the main T. gondii analog-sensitive kinase [12]. In silico prediction, an in vitro culture assay using transgenic parasites, and a structural analysis of TgCDPK1 all showed that TgCDPK1 is a target of BKI [6,8,12]. TgCDPK1 is involved in parasite attachment, invasion, egress, and secretion in vitro [5,6].…”
mentioning
confidence: 99%
See 1 more Smart Citation